DISSECTING JOURNALISTIC REPORTS IN CHALLENGING XENOPHOBIC PROTESTS: A CASE OF ROHINGYA EVICTION NEWS - Rahayu, Nurhadianty; Umniyyah, Zahratul; Wardhani, Yanuaresti Kusuma (ENGLISH JOURNAL, 2025)
Toward the end of 2023, there was a massive discussion about how a group of students from varied universities in Aceh, Indonesia, forced out Rohingya refugees from their shelter. Based on this event, there was global and local news coverage about this which reflects how power dynamics are at play. The dissection of the news pieces is done following van Dijk’s Critical Discourse Analysis. The findings hint at how the interwoven world of journalistic reports can act as the voice that challenge the multi-layered injustice and perpetual othering experienced by Rohingya refugees. We discuss and present how news pieces are produced and how the discourse about the intersectional marginalization of refugees intensifies and provokes action towards the perpetuation of injustices.